2004
DOI: 10.1111/j.1939-1676.2004.tb02620.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibrocartilaginous Embolic Encephalomyelopathy of the Brainstem and Midcervical Spinal Cord in a Dog

Abstract: A 4-year-old, 7-kg, female spayed Maltese dog was referred to the University of Missouri Veterinary Medical Teaching Hospital for acute onset of ataxia and left thoracic limb paralysis. The dog had been normal earlier that day when allowed outside but became ataxic and recumbent shortly after re-entering the house. She did not appear to be painful at that time. The dog had no prior history of illness and was current on all vaccinations.The general physical examination was within normal limits except for otitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 7 publications
0
18
0
1
Order By: Relevance
“…Two studies were excluded because spinal cord infarction was induced experimentally. Twenty-seven papers describing a total of 322 cases remained for analysis (Griffiths 1973, Zaki and others 1974, Griffiths and others 1975, De Lahunta and Alexander 1976, Greene and Higgins 1976, Zaki and Prata 1976, Hayes and others 1978, Chick 1979, Gill 1979, Kornegay 1980, Schubert 1980, Doige and Parent 1983, Gilmore and De Lahunta 1987, Penwick 1989, Dyce and Houlton 1993, Oliver 1993, Cauzinille and Kornegay 1996, Junker and others 2000, Hawthorne and others 2001, Gandini and others 2003, Axlund and others 2004,Grunenfelder and others 2005, Ueno and others 2005, De Risio and others 2007, De Risio and others 2008, Nakamoto and others 2009, Chung and others 2013). Two of these 27 papers included the same cases but presented different information about them; these cases were only counted once but data from both studies were utilised (De Risio and others 2007, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies were excluded because spinal cord infarction was induced experimentally. Twenty-seven papers describing a total of 322 cases remained for analysis (Griffiths 1973, Zaki and others 1974, Griffiths and others 1975, De Lahunta and Alexander 1976, Greene and Higgins 1976, Zaki and Prata 1976, Hayes and others 1978, Chick 1979, Gill 1979, Kornegay 1980, Schubert 1980, Doige and Parent 1983, Gilmore and De Lahunta 1987, Penwick 1989, Dyce and Houlton 1993, Oliver 1993, Cauzinille and Kornegay 1996, Junker and others 2000, Hawthorne and others 2001, Gandini and others 2003, Axlund and others 2004,Grunenfelder and others 2005, Ueno and others 2005, De Risio and others 2007, De Risio and others 2008, Nakamoto and others 2009, Chung and others 2013). Two of these 27 papers included the same cases but presented different information about them; these cases were only counted once but data from both studies were utilised (De Risio and others 2007, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, multifocal signs may be explained by the fact that emboli have the potential to shower multiple areas of the nervous system. Some cases, such as the dog with both spinal and caudal brainstem signs, had histopathological confirmation of multiple embolic lesions (Axlund and others 2004). Regardless of cause, the appearance of multifocal neurological signs on examination should not exclude FCE as a differential diagnosis in a patient who otherwise fits appropriate diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
“…computed tomography (CT) and magnetic resonance imaging (MRI)). The results for 49 dogs with CVA diagnosed by MRI have been reported, 1,4,5 and based on the imaging, 20 dogs had cerebellar infarcts, 4,5 17 had infarcts in the cerebrum, 4 had multifocal lesions and 8 infarcts were located in the thalamus or midbrain. 5,6 A variety of concurrent diseases potentially causing CVA have been identified in dogs, with the two most frequently reported being chronic renal disease and untreated hyperadrenocorticism.…”
mentioning
confidence: 97%
“…5,8,10,15 Cerebral infarction in dogs most commonly involves the territory of the middle cerebral artery, 16 similar to the prevalence in humans, 5,16 and is also more commonly ischaemic. 5,17…”
mentioning
confidence: 99%
“…In contrast to humans, both atherosclerosis and cardioembolic stroke are rare in dogs, although atherosclerosis has been associated with canine hypothyroidism and diabetes mellitus . There are, however, several underlying disorders associated with embolic stroke in dogs, including septic diseases (eg, endocarditis), parasites (eg, Dirofilaria immitis ), primary or metastatic neoplasia, and fibrocartilaginous embolism . In one retrospective study, a concurrent medical condition was found in 18/33 (54%) of dogs with brain infarcts, of which chronic kidney disease and hyperadrenocorticism were the most common .…”
mentioning
confidence: 99%